2005
DOI: 10.1242/jeb.01940
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of strain and activation in the thigh muscles of goats across gaits during level locomotion

Abstract: While in vitro studies of individual fibers, fiber bundles and whole muscles have greatly expanded our knowledge of the physiological properties and contractile mechanisms of skeletal muscle over the past 40·years, our understanding of how muscles actually operate in vivo is rather lacking in comparison. Consider the seemingly straightforward question of how much a given muscle changes length during any particular animal movement; for example, a limb muscle during a locomotor stride. Although detailed limb kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 30 publications
5
62
0
Order By: Relevance
“…We propose that the questions being addressed in a given study will dictate the importance of the regional variation outlined in this paper. It is true, however, that any study addressing regional variation (even if simply documenting its presence or absence) by sampling from multiple sites within a muscle will provide important information regarding muscle function [57]. We highlight three scenarios where quantifying regional variation will be important in future work.…”
Section: Functional Heterogeneity Within Musclesmentioning
confidence: 99%
“…We propose that the questions being addressed in a given study will dictate the importance of the regional variation outlined in this paper. It is true, however, that any study addressing regional variation (even if simply documenting its presence or absence) by sampling from multiple sites within a muscle will provide important information regarding muscle function [57]. We highlight three scenarios where quantifying regional variation will be important in future work.…”
Section: Functional Heterogeneity Within Musclesmentioning
confidence: 99%
“…A previous analysis of the net external (ground reaction) moments and work at the knee and ankle has provided some evidence that goats actively modulate joint work with surface grade; in particular, measurements on three goats showed that muscular moments at the knee and ankle contributed more positive work during uphill running and more negative work during downhill running then they did during level running (Lee et al, 2008). In another study on goats, Gillis and colleagues measured patterns of strain and activation in the biceps femoris and vastus lateralis muscles during level locomotion and showed that the amount of fascicle stretching and shortening (and presumably fascicle work) varied depending on locomotor speed (Gillis et al, 2005). Our ongoing research builds upon and extends these previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although fascicle strain rate varies with flight speed, the generally uniform contractile properties of the pectoralis across a range of flight speeds [27,29] (figure 3) reflect the strikingly uniform fibretype characteristics of the avian pectoralis [21 -23]. This is in contrast to the much larger change in fascicle shortening velocity with running speed that occurs in the leg muscles of terrestrial animals [51][52][53][54].…”
mentioning
confidence: 99%